Functional performance, maximal strength, and power characteristics in isometric and dynamic actions of lower extremities in soccer players - Requena, B.; Gonzalez-Badillo, J. J.; Vilareal, E. S. de S.; Ereline, J.; Garcia, I.; Gapeyeva, H.; Pääsuke, M. (The Journal of Strength and Conditioning Research, 2009)
The purposes of the present study were to determine muscle strength and power output characteristics in a group of professional soccer players and to identify their relationships with 2 functional performance tests (vertical jumping height and 15-m sprint time). Maximal strength and power indices attained against different loads in barbell back squat exercise, isometric maximal force of the knee extensor and plantar flexor muscles, isokinetic peak torque of the knee extensors muscles, vertical jumping height in squat and counter-movement jumps, and 15-m sprint time tests were assessed in 21 semiprofessional soccer players (age 20 ± 3.8 years). Correlation analyses were performed to examine the relationship between each of these measures. The main results of the present study were that (a) maximal power in concentric half-squat exercise was attained with a load of 60% of 1 repetition maximum, representing 112% of body weight; (b) the performance in the functional tests selected was significantly related with all the half-squat variables measured, especially with loads of 75-125% of body weight; and (c) low to nonsignificant correlations were found between functional tests performance and isometric and isokinetic muscle strength measures. It was concluded that in semiprofessional soccer players (a) isometric and isokinetic muscle strength assessed in an open kinetic chain were not movement-specific enough to predict performance during a more complex movement, such as jump or sprint and (b) concentric half-squat exercise was principally related with the functional tests selected when it was performed against external loading within the range of the load in case of which the maximal power output was attained.